2020
DOI: 10.1016/j.cmi.2020.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response against SARS-CoV-2 spike protein and nucleoprotein evaluated by four automated immunoassays and three ELISAs

Abstract: Objectives The aim was to determine the antibody response against SARS-CoV-2 spike protein and nucleoprotein using four automated immunoassays and three ELISAs for the detection of total Ig antibodies (Roche) or IgG (Abbott, Diasorin, Snibe, Euroimmun, Mikrogen) in COVID-19 patients. Methods Sensitivity and dynamic trend to seropositivity were evaluated in 233 samples from 114 patients with moderate, severe or critical COVID-19 confirmed with PCR on nasopharyngeal swab.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
138
3
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(160 citation statements)
references
References 29 publications
14
138
3
5
Order By: Relevance
“…In prior studies, the Abbott SARS-CoV-2 IgG assay has shown excellent performance characteristics with high specificity (99.1-99.9%) for prior infection with SARS-CoV-2 (20,49,50). Curiously, the positive predictive value for the Abbott SARS-CoV-2 IgG assay for neutralizing antibodies or protection in our population was only 50% (3/6 crewmembers).…”
Section: Serological Responses Among These Individuals As Measured Bymentioning
confidence: 61%
“…In prior studies, the Abbott SARS-CoV-2 IgG assay has shown excellent performance characteristics with high specificity (99.1-99.9%) for prior infection with SARS-CoV-2 (20,49,50). Curiously, the positive predictive value for the Abbott SARS-CoV-2 IgG assay for neutralizing antibodies or protection in our population was only 50% (3/6 crewmembers).…”
Section: Serological Responses Among These Individuals As Measured Bymentioning
confidence: 61%
“…Finally, we characterized cross-reactive T cell responses in just 1 unexposed HD, because HD9 was the only unexposed HD in our cohort with preexisting immunity to SARS-CoV-2. Although we screened this individual using 2 different SARS-CoV-2 antibody tests with stated sensitivities of 100% among hospitalized patients by 3 weeks after symptom onset (24,25), negative findings do not definitively prove that this individual did not have asymptomatic infection. This is important, given the studies showing that seronegative exposed individuals can have SARS-specific T cell responses (7,26), although the cross-reactivity we describe here may also explain those results.…”
Section: Discussionmentioning
confidence: 98%
“…ELISA methods are robust and can easily be automated as a load-and-go system, generating dozens of results in a couple of hours, but there is an inconclusive ("gray") zone with undetermined results. Other studies have compared ELISA tests for CoVID-19, with good sensitivity and great overall intermethod agreement (Elslande et al, 2020;Nicol et al, 2020;Theel et al, 2020). Despite the need of quantitative assessment of positive results, LFA is a quick and easy-to-handle method, which does not require specialized training prior to its implementation (Li Z. et al, 2020).…”
Section: Discussionmentioning
confidence: 99%